A comprehensive analysis of microRNA alteration in an ApoE(−/−) mice model of white adipose tissue injury induced by chronic intermittent hypoxia - Zhang, Jinjie; Guo, Yaopeng; Ji, Meilin; Lin, Shu; Liu, Dexin; Chen, Qingshi (Frontiers in Genetics, 2025)
BackgroundMicroRNAs (miRNAs) represent a class of noncoding small RNAs and are implicated in many diseases. However, the role of miRNA in obstructive sleep apnea (OSA)-induced white adipose tissue (WAT) dysfunction remains to be fully elucidated. Using miRNA sequencing (miRNA-seq), we uncovered the miRNA expression profiles in chronic intermittent hypoxia (CIH)-induced WAT dysfunction mice.MethodsWe established an apolipoprotein-deficient (ApoE−/−) CIH mouse model and identified differentially expressed miRNAs (DEmiRs) using miRNA-seq technology. With the help of Gene Ontology (GO) functional enrichment and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, we determined the biological functions of these DEmiRs. In addition, RT-qPCR was performed for further evaluation of the sequencing data. Finally, we constructed a conserved negative correlation (CNC) network to expound the relationship between miRNA and target genes.ResultsOverall, 13 miRNAs were found to be upregulated and 18 miRNAs downregulated in the CIH-induced mouse model of WAT dysfunction. KEGG pathway analysis results indicated that the lysosome pathway participated in CIH-induced WAT dysfunction. Then, eight miRNAs were shortlisted for RT-qPCR validation. Based on the data, we chose these DEmiRs to construct a miRNA–mRNA regulatory network.ConclusionOverall, we identified 31 DEmiRs in the ApoE−/− CIH mouse model. Our findings may play a major role in explaining the pathophysiological mechanisms of WAT dysfunction induced by obstructive sleep apnea.